2022
DOI: 10.3389/fvets.2022.819917
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Long Non-Coding RNA and mRNA Expression in the Jejunum of Lambs Challenged With Escherichia coli F17

Abstract: It has long been recognized that enterotoxigenic Escherichia coli (ETEC) is the major pathogen responsible for vomiting and diarrhea. E. coli F17, a main subtype of ETEC, is characterized by high morbidity and mortality in young livestock. However, the transcriptomic basis underlying E. coli F17 infection has not been fully understood. In the present study, RNA sequencing was conducted to explore the expression profiles of mRNAs and long non-coding RNAs (lncRNAs) in the jejunum of lambs who were identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Amongst the 35 protein-coding genes located in the first preserved region identified in the present study, is the LYPD8 gene, which has been suggested to play a role in intestinal immunity in mice (Hsu et al, 2021) and more recently in sheep (Chen et al, 2022). The HSPA4 gene, identified within the second most conserved region in the JER, is a heat shock protein (HSP) 70 gene and is well known for its integral role in cellular stress response to heat (Deb et al, 2014).…”
Section: Runs Of Homozygosity Detectedmentioning
confidence: 62%
“…Amongst the 35 protein-coding genes located in the first preserved region identified in the present study, is the LYPD8 gene, which has been suggested to play a role in intestinal immunity in mice (Hsu et al, 2021) and more recently in sheep (Chen et al, 2022). The HSPA4 gene, identified within the second most conserved region in the JER, is a heat shock protein (HSP) 70 gene and is well known for its integral role in cellular stress response to heat (Deb et al, 2014).…”
Section: Runs Of Homozygosity Detectedmentioning
confidence: 62%
“…The mRNA expression dataset used in this study was obtained from our previous research [ 18 ]; the raw data are available on: , PRJNA759095, accessed on 10 October 2022.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, lambs with different E. coli F17 susceptibility ( E. coli F17-antagonism and -sensitive, AN and SE) were identified in a challenge experiment, and we analyzed the jejunal microbiota diversity [ 17 ] and transcriptomic profiles [ 18 ] using RNA-seq and 16s rRNA-seq approaches, respectively. The present study consists of two parts, first, the jejunal metabolite composition E. coli F17 AN and SE lambs were profiled using UHPLC-MS/MS approach.…”
Section: Introductionmentioning
confidence: 99%
“…Ten healthy lambs in the high-dose challenge group (antagonistic type) and ten low-dose-challenged lambs with diarrhoea (sensitive type) were selected, according to intestinal pathological sections and the amount of bacterial adherence in the intestinal contents. Six lambs were selected as case and control groups in the antagonistic and sensitive groups [18]. Two mL of venous blood was taken in EDTA-K2 anticoagulant tubes and stored at −80 • C. Samples were named as containing A for the antagonistic type and not containing A for the susceptible type.…”
Section: Sample Collectionmentioning
confidence: 99%